Assessment of the Financial Condition of Selected Dairy Cooperatives during the COVID-19 Pandemic - Kondej, Magdalena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2022)
The aim of the article is to present the financial condition of selected dairy cooperatives using ratio analysis and selected discriminant models. The main objective of the paper is to assess the overall financial condition of dairy cooperatives during the COVID-19 pandemic (2020-2021) and earlier years (2017-2019). The author focused, on the one hand, on the assessment of the financial condition of a selected group and, on the other hand, on the link between the financial situation of selected dairy cooperatives and state aid during the changing economic reality caused by the SARS CoV-2 virus. The financial analysis for dairy cooperatives also reveals a broader comparative context in the time span before and during the COVID-19 pandemic. The research shows that the analysed dairy cooperatives, with the exception of OSM Jasienica Rosielna, did not have a negative financial results.